(untitled) (Indian Journal of Arid Horticulture, 2025)
The main role of vegetative propagation of cucurbits through stem cuttings is to maintain gynoecious and male sterile line (Pandey and Rai, 2006). Seed propagation of cucurbits requires new planting materials every year due to the loss of hybrid vigour and delayed flowering and fruiting. The availability of true to true type hybrid seed in local market is also difficult. However, rapid multiplication of cucurbits by stem cuttings has been the answer to such problem in cucurbits. Some perennial cucurbits like pointed gourd and kundru etc. as well as pumpkin (Singh, 1997), bottle gourd and bitter gourd (Singh, 2004) has been successfully propagated by stem cuttings.